GAMBARAN PENGGUNAAN OBAT ANTIDIABETIK PADA PENGOBATAN PASIEN DIABETES MELITUS TIPE II RAWAT JALAN DI RSUP DR WAHIDIN SUDIROHUSODO MAKASSAR - Hardianty Malinda; Rahmawati Rahmawati; Hendra Herman (Fakultas Farmasi UMI, 2015)
Diabetes mellitus is a chronic disesase characterized by high blood sugar levels in the body. This research aims to present the use of antidiabetic medication for type 2 diabetes mellitus in outpatient at RSUP Dr. Wahidin Sudirohusodo Makassar. This is a descriptive survey in the form of retrospective search. The results showed that the use of drugs by drug class and type of antidiabetic drugs sulfonylurea (glibenclamide 12.4%, glimepiride 7.2%, gliclazide 3.9%), biguanide (metformin 43.8%0, inhibitor α-glucosidase (acarbose 3.3%), thiazolidinedione (pioglitazone 0.7%), the combination of OHO (gliburida-metformin 0.7%), vildagliptin-metformin 0.7%), rapid insulin 8.5%, insulin detemir 13.1%, insulin glargine 4.6%, and insulin premix 13.1%.